2017
DOI: 10.1542/peds.2016-1758f
|View full text |Cite
|
Sign up to set email alerts
|

Digital Life and Youth Well-being, Social Connectedness, Empathy, and Narcissism

Abstract: Youth well-being, social connectedness, and personality traits, such as empathy and narcissism, are at the crux of concerns often raised about the impacts of digital life. Understanding known impacts, and research gaps, in these areas is an important first step toward supporting media use that contributes positively to youth's happiness, life satisfaction, and prosocial attitudes and behaviors. By examining existing work addressing these issues across domains, we found that a complex interplay of individual fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 22 publications
0
48
0
10
Order By: Relevance
“…In this respect, it is noteworthy that in empathy studies in young adults, a correlation between time spent with digital media and a lower cognitive empathy with other humans has been reported. 20 , 21 Whether due to lack of insight into what other people might think (theory of mind) or to problems with facial recognition or lack of exposure to peers (due to excessive online time) is not currently clear. It should be emphasized that some studies reported no correlation between online time and empathy (for reviews, see refs 22 and 23).…”
Section: Influences On the Developing Brainmentioning
confidence: 99%
“…In this respect, it is noteworthy that in empathy studies in young adults, a correlation between time spent with digital media and a lower cognitive empathy with other humans has been reported. 20 , 21 Whether due to lack of insight into what other people might think (theory of mind) or to problems with facial recognition or lack of exposure to peers (due to excessive online time) is not currently clear. It should be emphasized that some studies reported no correlation between online time and empathy (for reviews, see refs 22 and 23).…”
Section: Influences On the Developing Brainmentioning
confidence: 99%
“…Therefore, it can be said that there is a mutual relationship between family life satisfaction and community satisfaction. Social connectedness is one of the most basic needs of a human being (James et al 2017). Calmeiro et al (2018) investigated the effects of social and individual factors on life satisfaction (n = 3494 adolescents).…”
Section: Family Life Satisfaction and Social Connectednessmentioning
confidence: 99%
“…From an intrapersonal perspective, ICT is changing social interactions. Social media involves creating a digital life and personality which can affect young people's well-being (James et al, 2017). To respond to these challenges, digital skills now form part of the curriculum of schools and higher education institutions.…”
Section: Youth and Technologymentioning
confidence: 99%